Design of an ergonomic back support to prevent lumbar injuries - Solis Sparrow, Gino Leonardo (2024)
Low back pain is a widespread issue among individuals engaged in tasks requiring prolonged periods of static positioning. This musculoskeletal challenge has seen a surge in prevalence in recent times. The focal point of this study is to conceptualize an ergonomic support system specifically geared towards averting lumbar injuries linked to sedentary habits. Through a comprehensive experiment involving the analysis of existing ergonomic backrests and the subsequent development of a prototype using 3D scanning, design, and manufacturing processes, a solution was crafted. A study, incorporating a group of voluntary participants, was executed to assess the efficacy of the newly designed lumbar accessory. Findings reveal that the ergonomic product contributes to an increase in the duration of maintaining a correct posture, a reduction in pressure on crucial lumbar vertebrae (L4/L5 & L5/S1), and an overall enhancement in comfort levels. This innovation holds promise for addressing the escalating challenges associated with low back pain in the context of modern sedentary work environments. Therefore, the following question was asked: does the design of an ergonomic backrest prevent musculoskeletal injuries in the lower back in people who work at a desk and have a sedentary lifestyle? The methodological design of the study is based on an experimental approach. A prototype of an ergonomic back support is developed using 3D scanning design and fabrication, and its effectiveness is tested on a group of participants. The methodology includes comparing the performance of participants with and without the ergonomic backrest in a controlled environment, measuring variables such as posture, lumbar compression of the L4/L5 and L5/S1 vertebrae, and concentration during task performance.